Magnetic Nanowires: Toward Robust Segmented Nanowires: Understanding the Impact of Crystallographic Texture on the Quality of Segment Interfaces in Magnetic Metallic Nanowires (Adv. Mater. Interfaces 18/2016). Issue 18 (20th September 2016) - Zhang, Jin; Pané, Salvador; Sort, Jordi; Pellicer, Eva
Abstract : A detailed characterization of the interfaces in segmented nanowires made of hard‐magnetic CoPt and soft‐magnetic Ni, with and without the presence of Cu in between, obtained by sequential electrodeposition is reported by Jordi Sort, Eva Pellicer, and coworkers in article 1600336. Contrary to the CoPt/Cu interface, CoPt and Ni form a smooth and robust junction. The different textures observed have a decisive impact on the quality of the segment interfaces.